Paracoccidioidomycosis infection in domestic and wild mammals by Paracoccidioides lutzii. Issue 6 (10th March 2017) - Mendes, Josiara F.; Klafke, Gabriel B.; Albano, Ana Paula N.; Cabana, Ângela L.; Teles, Alessandra J.; de Camargo, Zoilo P.; Xavier, Melissa O.; Meireles, Mário Carlos A.
Summary: Paracoccidioidomycosis (PCM) is a systemic mycosis that occurs in several Latin American countries, especially in Brazil. It is caused by the thermo‐dimorphic fungus Paracoccidioides spp. Serological studies to detect animal infection represent an excellent strategy for data on the agent's ecology. Although the state of Rio Grande do Sul (RS) is an endemic area for PCM in humans, there is scarce information available on the ecology of the agent in the region. This study aimed to investigate the infection by Paracoccidioides lutzii in animals living in RS, Brazil. A total of 85 wild mammals, 200 horses and 196 domestic dogs, previously tested for infection by P. brasiliensis, were included in this study. Serum samples from the animals were tested by ELISA to detect anti‐ P. lutzii antibodies. From the 481 animals tested, 105 (21.8%) were seropositive for IgG anti‐ P. lutzii . Of these, 54 were also positive for P. brasiliensis . A total of 11 horses (10.5%), 30 dogs (28.8%) and 10 wild mammals (9.5%) were positive only for P. lutzii (n=51). The detection of anti‐ P. lutzii antibodies in animals of RS suggests that the fungus can be found in southern Brazil, despite being described mainly in the midwest and southeast of the country.